The Effect of Arm Strength, Leg Muscles, Torso Flexibility on The Improvement of Butterfly Stroke Swimming Exercise - Noor Noveminaila, Nabella Faradilla; Soegiyanto, Soegiyanto; Rahayu, Setya (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Butterfly stroke speed requires better muscle strength and flexibility from the swimmer than other swimming styles. This study aimed to analyze the effect of arm muscle strength, leg muscles, and torso flexibility on improving the results of butterfly swimming training in athletes.The research method used was the experiment with two groups, pretest-posttest design.The research sample consisted of 60 swimming athletes in Brebes Regency in 2019. Before being given the training program, the athletes were tested for the strength of the arm muscles, leg muscles, torso flexibility and butterfly speed of 50 meters, then given a butterfly swimming exercise with a frequency of 4x/week for 1 (one) month after participating in the training program and then testedthe swimming speed to see an improvement in training results. The results showed that r count (0.787)> r table (0.632) so that Hypothesis 1 (H1) was accepted, then r count (0.907)> r table (0.632) so that Hypothesis2 (H2) was accepted and r count (0.704)> r table (0.632) so that Hypothesis3 (H3) was accepted.The conclusion of this research is the butterfly stroke speed of 50 meters is significantly influenced by the strength of the arm muscles, leg muscle strength, and the flexibility of the athlete's foot.